Substrate Preference and Interplay of Fucosyltransferase 8 and N‑Acetylglucosaminyltransferases - Tseng, Tzu-Hao; Lin, Tzu-Wen; Chen, Chien-Yu; Chen, Chein-Hung; Lin, Jung-Lee; Hsu, Tsui-Ling; Wong, Chi-Huey (Journal of the American Chemical Society, 2017)
The core fucosylation of N-glycans on glycoproteins is catalyzed by fucosyltransferase 8 (FUT8) in mammalian cells and is involved in various biological functions, such as protein function, cancer progression, and postnatal development. The substrate specificity of FUT8 toward bi-antennary N-glycans has been reported, but it is unclear with regard to tri-antennary and tetra-antennary glycans. Here, we examined the specificity and activity of human FUT8 toward tri- and tetra-antennary N-glycans in the forms of glycopeptides. We found that the tri-antennary glycan [A3(2,4,2) type] terminated with N-acetylglucosamine (GlcNAc), which is generated by N-acetylglucosaminyltransferase (GnT)-IV, is a good substrate for FUT8, but the A3(2,2,6) type of tri-antennary glycan, generated by GnT-V, is not a substrate for FUT8. We also observed that core fucosylation reduced the activity of GnT-IV toward the bi-antennary glycan. Examining the correlation between the types of N-glycans and the expression levels of FUT8, GnT-IV, and GnT-V in cells revealed that these glycosyltransferases, particularly GnT-IV, play important roles in directing the branching and core fucosylation of N-glycans in vivo. This study thus provides insights into the interplay among FUT8, GnT-IV, and GnT-V in N-linked glycosylation during the assembly of glycoproteins.